Correlations between sympathetic nervous system activity and smoking, as well as unattended blood pressure in essential hypertension. (14th October 2021) - Manta, E; Konstantinidis, D; Dimitriadis, K; Tatakis, F; Drogkaris, S; Polyzos, D; Ntalakouras, I; Leontsinis, I; Thomopoulos, C; Tsioufis, K
Abstract: Background/Introduction: It is a well-known fact that the sympathetic nervous system is involved with the pathophysiology of hypertension. Smoking, which is one of the most significant risk factors for cardiovascular morbidity and mortality, also contributes to the development of hypertension mainly through the stimulation of the sympathetic nervous system. Moreover, measurement of unattended blood pressure (BP) may provide additional information compared to conventionally attended BP. Purpose: The aim of this study was to demonstrate the impact of smoking on sympathetic nervous system stimulation, and on BP measurement variations with and without medical supervision. Methods: We studied patients with essential hypertension, who were separated into two groups, depending on their smoking habits (Group I: non-smokers, Group II: smokers). In all participants, sympathetic drive was assessed by MSNA estimations based on established methodology (microneurography). Both unattended (patient alone in the room, an oscillometric device programmed to perform 3 BP measurements, at 1-minute intervals, after 5 minutes of rest) and attended BP measurements were conducted with the same device, on the same day of MSNA recording, in random order. Then, we compared the two BP measurement values of each patient to assess which of the two was higher. Results: Ninety-two consecutive patients (58±11 years, 50 males) were evaluated. Smokers (n=19) did not differ as regards 24-h ambulatory BP levels, glucose levels, renal function and left ventricular mass index when compared to non-smokers (n=73). However, higher levels of MSNA were recorded to smokers (73.16±13.42 vs. 61.04±18.10 bursts per 100 heartbeats, p<0.01). Furthermore, higher percentage of smokers recorded to have unattended BP values higher than attended (73.7% vs. 47.9% of them respectively, p=0.045). In particular, in smokers unattended BP was higher than attended by 10.07±6.7 mmHg, while in non-smokers unattended BP was lower than attended by 6.6±7.14 mmHg. No correlation was found between the MSNA and the differences observed in the two values resulting from the two different measurements of BP, maybe due to the small size of the sample. Conclusions: Cigarette smoking is accompanied with higher sympathetic nervous system activation. Moreover, smokers exhibit higher unattended blood pressure values than normal measurements. The emerging hypothesis is that the stimulation of the sympathetic system causes this difference in measurements. A larger sample of patients is needed to fully determine the clinical significance of the above observation. Funding Acknowledgement: Type of funding sources: None.